2016
DOI: 10.7314/apjcp.2015.16.18.8031
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Receptors : New Target in Breast Cancer

Abstract: Background: Preclinical studies have demonstrated that β-adrenergic receptor antagonists could improve the prognosis of breast cancer. However, the conclusions of clinical and pharmacoepidemiological studies have been inconsistent. This review was conducted to re-assess the relationship between beta-adrenoceptor blockers and breast cancer prognosis. Materials and Methods: The literature was searched from PubMed, EMBASE and Web of Nature (Thompson Reuters) databases through using key terms, such as breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
(121 reference statements)
1
4
0
Order By: Relevance
“…Similar findings were also reported in studies of hemangioma, neuroblastoma, melanoma and gastric cancer [49][50][51][52]. Chang et al go as far as to support the use of β-blockers as a possible novel therapeutic intervention, but that claim must be utilized with caution, as recent studies by Wang et al stated that B2 adrenergic stimulation with norepinephrine has actually attenuated invasion of certain types of breast CA's migration [53]. Thus despite overwhelming evidence that B-adrenergic stress responses is pro-cancerous, there is still need to quantify the exact types of cancers that are amenable to this type of therapy.…”
Section: Blood Transfusionsupporting
confidence: 61%
“…Similar findings were also reported in studies of hemangioma, neuroblastoma, melanoma and gastric cancer [49][50][51][52]. Chang et al go as far as to support the use of β-blockers as a possible novel therapeutic intervention, but that claim must be utilized with caution, as recent studies by Wang et al stated that B2 adrenergic stimulation with norepinephrine has actually attenuated invasion of certain types of breast CA's migration [53]. Thus despite overwhelming evidence that B-adrenergic stress responses is pro-cancerous, there is still need to quantify the exact types of cancers that are amenable to this type of therapy.…”
Section: Blood Transfusionsupporting
confidence: 61%
“…[28,29,64,[67][68][69][70][71] The potential usefulness of beta-blockers for adjuvant cancer treatment has additionally been discussed in depth based by comprehensive reviews of published preclinical and clinical literature. [67,72,73] By contrast, the current review analyzes mechanistic aspects of G s -coupled receptors and their physiological inhibitors and their modulating effects on cancer. The discrepancies between preclinical and clinical findings are thus not only triggered by the potential sensitization of β-ARs in response to long-term beta-blocker therapy (decades of treatment in people as opposed to a few weeks in experimental animals), but also by the potential impact of factors unrelated to β-ARs.…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of ΑDR-β in some breast cancer cell types affects the recurrence and metastasis of breast cancer, suggesting that blocking the ΑDR-β pathway is an effective strategy to slow down the progression of breast cancer [105] . A meta-analysis by Wang et al., a retrospective analysis by Zhao et al., a systematic analysis of cohort studies of breast cancer by Childers et al., and a clinical study analysis by Choy evaluated the relationship between ΑDR-β antagonists and breast cancer prognosis [32 , 33 , 149 , 165] . The results showed that BBS significantly reduced the risk of recurrence and distant metastasis, but most of these studies involved small samples and the follow-up time was relatively short; thus, larger studies are needed to further explore the relationship between BBS and breast cancer prognosis.…”
Section: Research Progress Of the Treatment Of Breast Cancer By Drugs Affecting The Neuroendocrine Systemmentioning
confidence: 99%